HUBUNGAN PENGGUNAN GADGET DENGAN KUALITAS TIDUR PADA REMAJA KELAS VII DI SMP NEGERI 1 BLITAR: bahasa indonesia - Rahma, Kartika Dwi; Anjaswari, Tri; Sulastyawati, Sulastyawati; Wiyono, Joko (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Gadgets are the latest technology created with various applications that can present various news media, social networks and even entertainment. The high use of gadgets among teenagers due to technological developments requires teenagers to use gadgets every day. High use of gadgets at night such as time of use, duration of use, and activity using gadgets is one of the factors that affect sleep quality in adolescents. This study aims to determine the relationship of the use of gadgets with sleep quality in adolescents at SMP Negeri 1 Blitar. This type of correlational research with Cross Sectional approach. It was held at SMPN 1 Blitar with a total of 40 respondents, which were taken by purposive sampling technique. The sample is class VII students who actively use gadgets for at least 3-6 months. Analysis to determine the relationship between variables using the spearman-rho test. The results of this study found that respondents with high gadget use were 45%. And most of the respondents included in the low category of 37.5%, which means that most teenagers have difficulty sleeping. From the results of statistical tests, the value of p = 0.001 and the value of r = 0.509. The use of gadgets has a significant relationship with sleep quality in seventh grade adolescents at SMPN 1 Blitar. Teenagers begin to lose social time due to the use of gadgets that are interested in the applications in it.